New approach for paper-based microchannel fabrication by inkjet printing technology. (24th May 2019) - Le, Ngan Nguyen; Phan, Hue Cam Thi; Tran, Huong Kim; Dang, Dung My Thi; Dang, Chien Mau
Microfluidic chip in general and paper-based microfluidic chip in particular have attracted much scientific interest recently due to their potential applications. Paper-based microfluidics, or lab-on-paper, have many advantage features such as low cost, easy to use, portability and disposability. There are two popular methods using inkjet printing technology to fabricate microchannel on paper substrate: direct and indirect method. In this paper, a different approach is proposed to fabricate microchannels on nitrocellulose substrate. Glycol ether solution-based ink is inkjet-printed on a paper substrate to dissolve the substrate and form hydrophobic lines. For this, glycol ether solution-ink is first prepared to obtain suitable viscosity for our piezoelectric inkjet printer. After that, a form with a triangle shape is printed using this ink with different parameters of inkjet printer. A simple leakage test is performed to evaluate the quality of hydrophobic lines. The results of field emission-scanning electron microscopy (FE-SEM) images and leakage test show that 305 μm wide hydrophobic lines are already formed and printed triangle can avoid the leakage of water. Therefore, this method can be used to fabricate paper-based microchannels for microfluidic paper-based analytical devices (μPADs) applications in the future.